A micro‐process model of institutional complexity in public hybrid organizations: Construal of identity threats and mitigation strategies. (17th November 2020) - Shams, Farshid
Abstract: This article analyses how non‐managerial professionals in public service organizations experience the tension between managerial and professional institutional logics and manage to minimize it through identity work. By studying how academics in ten Canadian public universities talk about their routine work activities, it is found that they interpret the institutional contradictions between these logics as threats to their identities and mitigate them by undertaking discursive strategies to author legitimate selves. Three mitigation strategies of delegitimization, selective identification and appropriation of realized publicness are identified. These findings are synthesized in a process model of construal and response that illustrates a set of micro‐practices of professionals by which the institutional hybridity is maintained. By moving beyond professionals' resistance and hybridization (integrating the two logics) and identifying a recursive relational positioning mechanism as a way of coping with institutional complexity, this study complements previous findings in the growing literature on organizing professionalism.